Group psychedelic therapy: empirical estimates of cost-savings and improved access - Marseille, Elliot; Stauffer, Christopher S.; Agrawal, Manish; Thambi, Paul; Roddy, Kimberly; Mithoefer, Michael; Bertozzi, Stefano M.; Kahn, James G. (Frontiers in Psychiatry, 2023)
Objective To compare group and individual psychedelic-assisted therapy in terms of clinician time, costs and patient access. Methods Using 2023 data from two group therapy trial sites, one using 3,4-Methylenedioxymethamphetamine (MDMA) to treat posttraumatic stress disorder (PTSD), and one using psilocybin to treat major depressive disorder (MDD), we compared overall variable costs, clinician costs and clinician time required by therapy protocols utilizing groups versus individual patient therapy. Using published literature, we estimated the prevalence of adults with PTSD and MDD eligible for treatment with psychedelic therapy and projected the savings in time and cost required to treat these prevalent cases. Results Group therapy saved 50.9% of clinician costs for MDMA-PTSD and 34.7% for psilocybin-MDD, or $3,467 and $981 per patient, respectively. To treat all eligible PTSD and MDD patients in the U.S. in 10 years with group therapy, 6,711 fewer full-time equivalent (FTE) clinicians for MDMA-PTSD and 1,159 fewer for FTE clinicians for psilocybin-MDD would be needed, saving up to $10.3 billion and $2.0 billion respectively, discounted at 3% annually. Conclusion Adopting group therapy protocols where feasible would significantly reduce the cost of psychedelic-assisted therapies. By enhancing the number of patients served per clinician, group therapy could also ameliorate the anticipated shortage of appropriately trained clinicians, thereby accelerating access to these promising new therapies.